2017
DOI: 10.3390/catal7020039
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Analysis of Water Oxidation Catalyst cis-[Ru(bpy)2(H2O)2]2+: Effect of Dimerization

Abstract: While the catalytic activity of some Ru-based polypyridine complexes in water oxidation is well established, the relationship between their chemical structure and activity is less known. In this work, the single site Ru complex [Ru(bpy) 2 (H 2 O) 2 ] 2+ (bpy = 2,2 -bipyridine)-which can exist as either a cis isomer or a trans isomer-is investigated. While a difference in the catalytic activity of these two isomers is well established, with cis-[Ru(bpy) 2 (H 2 O) 2 ] 2+ being much more active, no mechanistic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 30 publications
3
27
0
Order By: Relevance
“…Interestingly, recent computational studies on molecular Ir complexes , found that formation of the high-valent Ir VI intermediates is plausible in the experiments and facilitates the OER catalysis . It is also worth noting that such proposed Ir VI intermediates are isoelectronic to Ru V species, which are proposed to play important role in molecular OER catalysts. , …”
Section: Resultsmentioning
confidence: 92%
“…Interestingly, recent computational studies on molecular Ir complexes , found that formation of the high-valent Ir VI intermediates is plausible in the experiments and facilitates the OER catalysis . It is also worth noting that such proposed Ir VI intermediates are isoelectronic to Ru V species, which are proposed to play important role in molecular OER catalysts. , …”
Section: Resultsmentioning
confidence: 92%
“…[3] To date, the most extensive mimic of that process was achieved with Ru based water oxidation catalysts. [4] However, first row transition metals and especially Fe based water oxidation catalysts carry a great promise as they utilize earth abundant elements. [5] An example of a notably durable Fe-based water oxidation catalyst is [Fe(Pytacn)(OTf) 2 ] (Pytacn = 1-(2'-pyridylmethyl)-4,7-dimethyl-1,4,7-triazacyclononane and OTf = -SO 3 CF 3 ) (1), which catalyzes the water oxidation reaction using Ce IV (Cerium, ammonium nitrate, CAN) or NaIO 4 as oxidants.…”
mentioning
confidence: 99%
“…Fe V (d 3 ) is isoelectronic to Ru V (d 3 ): the species which are also very short lived but can be observed in situ at selected conditions . Moreover, depending on the reaction conditions, Ru V =O species can form the O−O bond via both radical coupling (RC) and water nucleophilic attack (WNA) pathways . Current experiments show that [Fe V =O,(OH) (Pytacn)] 2+ reacts with water via WNA on the oxo ligand, assisted by an initial hydrogen bond interaction of the water molecule with the cis ‐ positioned hydroxide ligand …”
Section: Figurementioning
confidence: 99%
“…Follow up spectroscopic experiments did not identify spectroscopic signatures of 2 in the reaction mixtures, suggesting that this species must be very short lived. Fe V (d 3 ) is isoelectronic to Ru V (d 3 ): the species which are also very short lived but can be observed in situ at selected conditions . Moreover, depending on the reaction conditions, Ru V =O species can form the O−O bond via both radical coupling (RC) and water nucleophilic attack (WNA) pathways .…”
Section: Figurementioning
confidence: 99%